1993
DOI: 10.1897/1552-8618(1993)12[1763:eoalnf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Laboratory-Generated Noec for Linear Alkylbenzene Sulfonate in Outdoor Experimental Streams

Abstract: Laboratory and field studies were conducted with linear alkylbenzene sulfonate (LAS) to evaluate the use of laboratory-generated NOECs for protecting aquatic organisms in outdoor experimental streams. Fathead minnows (Pimephalesprornelus) and freshwater amphipods (Hyulellu azteca) were exposed in the laboratory to an environmentally realistic mixture of LAS (average chain length C,, 9) for 7 d; fathead minnows were also exposed in a 28-d study. Calculated NOEC values based on survival and growth ranged from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…NOEC and LOEC values are used extensively in risk assessments to identify contaminants posing risk to organisms (Fairchild et al 1993). Although there is some question over the applicability of NOEC and LOEC values for regulatory uses (Laskowski 1995), they are useful as benchmarks to identify contaminants of greatest concern in screening level risk assessments (Campbell and Hoy 1996).…”
Section: Discussionmentioning
confidence: 99%
“…NOEC and LOEC values are used extensively in risk assessments to identify contaminants posing risk to organisms (Fairchild et al 1993). Although there is some question over the applicability of NOEC and LOEC values for regulatory uses (Laskowski 1995), they are useful as benchmarks to identify contaminants of greatest concern in screening level risk assessments (Campbell and Hoy 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A review by Venhuis and Mehrvar [22] regarding the acute effects of LAS on freshwater plankton and organisms (including bacteria to crustaceans) under field conditions revealed that LAS has a negative impact on the survival of heterotrophic nanoflagellates and ciliates at very low concentrations. Fairchild et al [23] has also found that LAS concentration of 0.36 mg/L had no effect on biological population. Schroder [24] determined LAS concentrations under realistic worst-case conditions (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…van de Plassche et al The PNEC value of 0.32 mg/L, based on single-species laboratory test results, is in good agreement with the NOEC from field studies of 0.25 to 0.50 mg/L. Several field studies showed minor effects at concentrations at the lower limit of this range: Lewis [28], NOEC of 0.24 mg/L for relative abundance of phytoplankton; Lewis and Hamm [27], NOEC of 0.09 mg/L for photosynthetic response of phytoplankton; Chattopadhyay and Konar [29], NOEC Ͻ0.25 mg/L for number and wet weight of chironomids; Fairchild et al [30], NOEC Ͻ0.36 mg/L for fish growth and survival; and Tattersfield et al [26], NOEC of 0.12 mg/L. Thus, a final PNEC of 0.25 mg/L, equal to the lower limit of the field NOECs, is derived for C 11.6 LAS.…”
Section: Comparison Of Pnec Based On Single-species Laboratory Studiementioning
confidence: 99%